RECEIVING ACHIEVED IN BANKRUPTCY ORIGIN FROM SUSPENSION OF DEBT PAYMENT OBLIGATIONS - Horman Siregar (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
Law No. 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt (PKPU) only prohibits debtors from submitting a reconciliation plan if declared bankrupt based on Article 285, Article 286 and Article 292. Thus, the decision to declare bankruptcy resulting from other than the provisions of Article 285, Article 286 and Article 291 of the Bankruptcy and PKPU Law, it is still permissible to propose a reconciliation plan in bankruptcy in accordance with the provisions of Article 144 of the Bankruptcy and PKPU Law. Article 144 of the Bankruptcy Law & PKPU states that every bankrupt debtor has the right to offer peace to all of his creditors. That is, the settlement can be offered by the debtor after the debtor is declared bankrupt by the Commercial Court. This research aims to answer legal issues regarding the legal position of debtors and creditors in bankruptcy after the rejection of the peace plan in the PKPU process. To answer the research problem, this study uses a type of normative legal research with a statutory approach, a conceptual approach, and a case approach in the form of a Surabaya Commercial Court decision which has permanent legal force. The data used are secondary data in the form of primary, secondary and tertiary materials, obtained through library research or document studies. The results of this study indicate that debtors and creditors can still reach peace even though the Commercial Court has declared the debtor in a state of bankruptcy originating from PKPU. The legal considerations of the panel of judges in ratifying the reconciliation of PT Anugrah Kembang Sawit Sejahtera in bankruptcy originating from PKPU as stated in Decision No. 59/Pdt.Sus-PKPU/2019/PN.Niaga.Sby at the Commercial Court at the Surabaya District Court is the result of voting for a bankruptcy debtor's settlement proposal that has been approved by creditors in accordance with Article 151 of the Bankruptcy Law and PKPU which is then set forth in a peace agreement. In addition, the Court did not find any reasons for refusing to ratify the settlement in accordance with Article 159 paragraph (2) of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt, the court is obliged to give a decision regarding the ratification of the settlement.